perencanaan arsitektur sistem informasi dengan menggunakan metode enterprise architecture planning (EAP) pada UD. AMANJAYA 03 DAYEUHLUHUR - Agitya Pujiandri, Dea; Dwicahya Supriatman, Rian; Mulyana , Dadan (Fakultas Teknik Jurusan Sistem Informasi Universitas Galuh, 2025)
Seeing the increase in demand from the general public for the use or processing of wood, UD. Amanjaya 03 exists as a timber company engaged in the trading business. UD. Amanjaya focuses on selling raw goods, namely selling wood in the form of logs and logs and only carrying out the process of buying and selling wood, cutting and marketing. However, employee payroll and attendance processes still use manual processes. It is hoped that this research can become evaluation material for entrepreneurs in carrying out their business activities. On this basis, the researcher proposed the research title,